Signature of pressure-induced topological phase transition in ZrTe5 - Kovács-Krausz, Zoltán; Nagy, Dániel; Márffy, Albin; Karpiak, Bogdan; Tajkov, Zoltán; Oroszlány, László; Koltai, János; Nemes-Incze, Péter; Dash, Saroj P.; Makk, Péter; Csonka, Szabolcs; Tóvári, Endre (npj quantum materials, 2024)
The layered van der Waals material ZrTe 5 is known as a candidate topological insulator (TI), however its topological phase and the relation with other properties such as an apparent Dirac semimetallic state is still a subject of debate. We employ a semiclassical multicarrier transport (MCT) model to analyze the magnetotransport of ZrTe 5 nanodevices at hydrostatic pressures up to 2 GPa. The temperature dependence of the MCT results between 10 and 300 K is assessed in the context of thermal activation, and we obtain the positions of conduction and valence band edges in the vicinity of the chemical potential. We find evidence of the closing and re-opening of the band gap with increasing pressure, which is consistent with a phase transition from weak to strong TI. This matches expectations from ab initio band structure calculations, as well as previous observations that CVT-grown ZrTe 5 is a weak TI in ambient conditions.